臺灣高中教育資源管理均等性之評估 Assessing the Equality of Senior High School Educational Resources Management in Taiwan - 張鈿富 Dian-Fu Chang; 鄧進權 Chin-Chuan Teng; 林孟潔 Meng-Jie Lin (Journal of Research in Education Sciences, 2010)
本文旨在發展高中教育資源管理績效評估指標，以作為探討高中教育資源管理均等性之衡量。研究者透過模糊權重發展高中教育資源管理之績效指標，依據權重排序選出十五項投入指標與五項產出指標，作為評估高中教育資源管理績效之參考，再運用這些指標透過Gini係數（Gini coefficient）進行各高中教育資源均等性之檢定。本文主要發現包括：一、以模糊權重發展之教育資源管理績效評估指標，可作為評估高中教育資源管理績效之工具；二、透過Gini 係數檢視高中教育資源之均等性，可提供主管教育機關與學校經營者更明確的改善訊息。 The purposes of this article were to explore the assessment indicators for senior high school educational resources management and to discuss the equality issues of those schools in Taiwan. The researchers applied the fuzzy weighting methods to assess the indicators of senior high school educational resources management for better performed, it is including 15 input and 5 output indicators. The Gini coefficients were used to exame the equality of their resource allocations in different senior high schools. The findings in the article are as follows: (1) The fuzzy weighting can be used to build the indicators system for assceesing the senior high school educational resources management, and the system can be used for policy tools to evaluate the resource management; (2) Gini coefficients as indices can be used to inspect the distributive equality, which will provide more clear pictures for the educational authories and school leaders to improve the equality problems in high schools.